2.1.6 \hline Use \( \cos (\alpha-\beta) \) to derive a formula for \( \sin (\alpha+\beta) \). (Hint: use co-function) in degrees
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To derive a formula for \( \sin (\alpha + \beta) \), we start by using the co-function identity that states \( \sin(\theta) = \cos(90^\circ - \theta) \). Applying this to \( \sin(\alpha + \beta) \): \[ \sin(\alpha + \beta) = \cos(90^\circ - (\alpha + \beta)) = \cos(90^\circ - \alpha - \beta) \] Next, we simplify \( \cos(90^\circ - \alpha - \beta) \) using the cosine subtraction formula: \[ \cos(90^\circ - (\alpha + \beta)) = \cos(90^\circ - \alpha - \beta) = \sin(\alpha + \beta) \quad \text{(using the co-function identity)} \] Now, applying the cosine subtraction identity: \[ \cos(\alpha - \beta) = \cos \alpha \cos \beta + \sin \alpha \sin \beta \] Therefore, we can conclude that: \[ \sin(\alpha + \beta) = \sin \alpha \cos \beta + \cos \alpha \sin \beta \] Thus, the derived formula is: \[ \sin(\alpha + \beta) = \sin \alpha \cos \beta + \cos \alpha \sin \beta \]